THE EFFECTIVENESS OF LEARNING PROCEDURE TEXT IN SPEAKING PRACTICE BY USING VIDEO VLOG AT SMPN 7 MUARA BUNGO - Renda Lestari; Winda Trisnawati; Umul Fatihatun Nisa (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
Most of the students in junior high school find it difficult to learn English, when asked to practice speaking in a text procedure in front of the class they feel afraid and not confident. This research aims to find out the effectiveness of learning procedures text in speaking practice by using a video vlog at SMPN 7 Muara Bungo. The methodology of this research is quasi-experimental quantitative research. The analysis method uses data collection descriptive analysis speaking test. The participant of this study is 28 respondents from class 9.3 SMPN 7 Muara Bungo. To retrieve the data, the researchers used the rubric of learning procedures text in speaking practice. The result of this study was obtained to see whether video vlogs have effectiveness in improving students’ English speaking ability in the practice of procedure text, in speaking English students often feel insecure so students are lazy to speak English, especially in front of their friends. the researcher found that using video vlogs as a medium to improve students speaking ability was not effective, research results show that ttest – 4,824>ttable 1,703.